Currency Politics : The Political Economy of Exchange Rate Policy - Frieden, Jeffry A. (Princeton Princeton University Press, 2015)
The exchange rate is the most important price in any economy, since it affects all other prices. Exchange rates are set, either directly or indirectly, by government policy. Exchange rates are also central to the global economy, for they profoundly influence all international economic activity. Despite the critical role of exchange rate policy, there are few definitive explanations of why governments choose the currency policies they do. Filled with in-depth cases and examples, Currency Politics presents a comprehensive analysis of the politics surrounding exchange rates. Identifying the mo.
Include Reference and Index
Keywords: Foreign exchange rates -- History -- Commercial policy -- History